DAMPAK TRANSFORMSI DIGITAL TERHADAP MOBILITAS SOSIAL PADA MASYARAKAT PEDESAAN PERSPEKTIF FILSAFAT MANUSIA (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
Digital transformation is a systemic shift that affects various aspects of human life, includingsocial mobility in rural communities. Digital technologies offer new opportunities for accessto education, information, and employment that were previously limited for people living inrural areas. However, not all individuals are equally able to take advantage of theseopportunities. From the perspective of philosophical anthropology, particularly through theunderstanding of humans as thinking beings (homo sapiens) and free beings (homo liberum),digital transformation requires reflective thinking, autonomy in decision-making, and moralresponsibility in the use of technology. Social mobility is not merely seen as material movementbetween social classes but also as the actualization of human potential within the digital space.Therefore, the role of technology in supporting rural life greatly depends on the extent to whichindividuals can think critically, adapt meaningfully, and regard technology as a means toachieve a more meaningful and dignified existence. This abstract highlights that digitaltransformation, when integrated with human values and philosophical reflection, can serve asan ethical and functional instrument in promoting inclusive and dignified social mobility inrural communities.
Keywords: digital transformation, social mobility, rural society, philosophical anthropology, homo sapiens, ethical reflection